An Unusual Presentation of Osteogenesis Imperfecta: A Case Report. Issue 4 (October 2021) - Lindsay, Sarah E.; Nicol, Lindsey E.; Gamayo, Ashley C.; Raney, Ellen M.
Abstract : Case: We report an 18-year-old patient with a clinical phenotype consistent with severe osteogenesis imperfecta (OI) with frequent fractures, short stature, shortening and bowing of extremities, and unusual radiographic features of severe fibrous dysplasia, including lytic lesions and a "ground-glass" appearance. Genetic testing for the patient was notable for a c.119C>T (p.Ser40Leu) variant in exon 1 of IFITM5 and a c.676C>A (Pro226Thr) variant in exon 5 of CREB3L1 . Conclusion: This unusual skeletal presentation was in the setting of a rare IFITM5 mutation and represents a unique case of severe OI.